Efektivitas Modul Kesetimbangan Kimia Berbasis Guided Discovery Learning terhadap Hasil Belajar Peserta Didik - Efwah Yuli Fitri Said; Yerimadesi Yerimadesi (Universitas Negeri Padang, 2021)
This study aims to analyse the effectiveness of the chemical equilibrium module based on guided discovery learning on the learning outcomes of students. The study design uses a randomized control-group pretest-posttest design with quasi-experimental type. The population consisted of grade XI students of SMAN 1 Tigo Nagari in the 2019 till 2020 school year and samples were taken using simple random sampling technique. The research instrument was in the form of multiple choice tests, the data were analysed by n-gain test and hypothesis testing by t test. Based on the analysis of the data obtained n-gain experimental class is higher than the control class with a medium category and the hypothesis test obtained sig (2-tailed) less than 0,05. Analysis of these data concludes the hypothesis is accepted in other words the use of a chemical equilibrium module based on guided discovery learning is effective in improving student learning outcomes in class XI of SMAN 1 Tigo Nagari.